EXPLORING THE RELATIONSHIP BETWEEN PREREQUISITE CONCEPTUAL UNDERSTANDING AND MATHEMATICAL CREATIVE THINKING IN STRAIGHT-LINE EQUATIONS - Nahdiatul Latifa; Aditya Prihandhika; David Pratama (Universitas Muhammadiyah Metro, 2026)
This study was motivated by the still-low ability of students to understand prerequisite concepts and explore various problem-solving strategies in the topic of straight-line equations. The study aims to examine the relationship between the ability to understand prerequisite concepts and the mathematical creative thinking skills of junior high school students in the topic of straight-line equations. The study employed a quantitative approach with a correlational design involving 34 eighth-grade students at a private junior high school in Cirebon Regency. The sample was selected using purposive sampling. Data were collected through tests assessing conceptual understanding and mathematical creative thinking skills. Data analysis was conducted using the Spearman’s rank correlation test and K-Means Clustering. The analysis results indicate a significant positive correlation of moderate strength between conceptual understanding and mathematical creative thinking, with a correlation coefficient of 0.499. Analysis of student responses revealed that the characteristics of mathematical creative thinking do not differ significantly across different levels of conceptual understanding. These findings indicate that high conceptual understanding does not fully guarantee the optimal development of all indicators of mathematical creative thinking. The research results imply that mathematics instruction should not only emphasize conceptual mastery but also provide students with opportunities to explore various problem-solving strategies and develop new ideas in problem-solving. Kemampuan siswa dalam memahami konsep prasyarat dan mengeksplorasi berbagai strategi penyelesaian pada materi persamaan garis lurus perlu ditingkatkan. Penelitian ini bertujuan untuk menganalisis hubungan antara kemampuan pemahaman konsep prasyarat dan kemampuan berpikir kreatif matematis siswa SMP. Penelitian menggunakan pendekatan kuantitatif dengan jenis korelasional terhadap 34 siswa kelas VIII di SMP NU Lemahabang. Data diperoleh melalui tes uraian kemampuan pemahaman konsep dan kemampuan berpikir kreatif matematis. Analisis hubungan antarvariabel dilakukan menggunakan uji Rank Spearman, lalu metode K-Means Clustering digunakan untuk mengelompokkan siswa berdasarkan tingkat kemampuan pemahaman konsep sehingga hubungan pada setiap kelompok dapat dianalisis. Hasil penelitian menunjukkan terdapat hubungan positif yang signifikan dengan kekuatan sedang antara kemampuan pemahaman konsep dan kemampuan berpikir kreatif matematis pada seluruh sampel. Setelah dilakukan pengelompokan menggunakan K-Means Clustering berdasarkan tingkat kemampuan pemahaman konsep, hubungan pada setiap klaster tidak menunjukkan signifikansi statistik. Analisis jawaban siswa menunjukkan bahwa karakteristik kemampuan berpikir kreatif matematis pada setiap klaster tidak sepenuhnya berbeda. Temuan ini mengindikasikan bahwa kemampuan pemahaman konsep yang tinggi belum sepenuhnya menjamin berkembangnya kemampuan berpikir kreatif matematis secara optimal. Oleh karena itu, pembelajaran matematika perlu memberikan kesempatan kepada siswa untuk mengeksplorasi berbagai strategi penyelesaian masalah.